P4HB, a Novel Hypoxia Target Gene Related to Gastric Cancer Invasion and Metastasis. - Zhang, Jun; Guo, Shuai; Wu, Yue; Zheng, Zhi-chao; Wang, Yue; Zhao, Yan (BioMed Research International, 2019)
Gastric cancer (GC) is a common tumor-associated lethal disease, and invasiveness and metastasis are primary challenges in its clinical treatment. Hypoxia microenvironment cannot be ignored in the process of metastasis. Hypoxia inducible factor-1α (HIF-1α) is the core component of the hypoxia signaling pathway. The aim of this study was to identify potential hub genes and signaling pathways associated with HIF-1α. We explored the invasiveness- and metastasis-associated phenotype of GC via bioinformatics analysis and molecular studies. Differentially expressed genes (DEGs) were identified in GC cells and HIF-1α-knockdown GC cells. Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses were performed, and a protein-protein interaction (PPI) network was constructed. Hub genes were identified via centrality analysis and Molecular Complex Detection (MCODE) module analysis. The findings suggested that prolyl 4-hydroxylase beta polypeptide (P4HB) has strong associations with HIF-1α. Further, we observed that HIF-1α and P4HB were upregulated in SGC-7901 and BGC-823 cells. In addition, inhibition of HIF-1α expression reduced invasion and metastasis in GC cells; this effect was partially reversed by P4HB overexpression. Our results confirm that P4HB plays a significant role in the regulatory network of HIF-1α. Therefore, HIF-1α and P4HB may be considered potential biomarkers of GC.